The HST–Gaia Near-infrared Astrometric Reference Frame Near the Milky Way Galactic Center - Matthew W. Hosek Jr.; Tuan Do; Gregory D. Martinez; Rebecca Lewis-Merrill; Andrea M. Ghez; Jessica R. Lu; Shoko Sakai; Jay Anderson (The Astrophysical Journal)
We present the first high-precision proper-motion catalog, tied to the International Celestial Reference System (ICRS), of infrared astrometric reference stars within R ≤ 25″ (1 pc) of the central supermassive black hole at the Galactic center (GC). This catalog contains ∼2900 sources in a highly extinguished region that is inaccessible via Gaia. New astrometric measurements are extracted from Hubble Space Telescope (HST) observations (14 epochs, 2010–2023) and transformed into the ICRS using 40 stars in common with Gaia-DR3. We implement a new method for modeling proper motions via Gaussian processes that accounts for systematic errors, greatly improving measurement accuracy. Proper-motion and position measurements reach precisions of ∼0.03 mas yr ^−1 and ∼0.11 mas, respectively, representing a factor of ∼20 improvement over previous ICRS proper-motion catalogs in the region. These measurements define a novel HST–Gaia reference frame that is consistent with Gaia-CRF3 to within 0.025 mas yr ^−1 in proper motion and 0.044 mas in position, making it the first ICRS-based reference frame precise enough to probe the distribution of extended mass within the orbits of stars near SgrA*. In addition, HST-Gaia provides an independent test of the radio measurements of stellar masers that form the basis of current GC reference frames. We find that the HST–Gaia and radio measurements are consistent to within 0.041 mas yr ^−1 in proper motion and 0.54 mas in position at 99.7% confidence. Gaia-DR4 is expected to reduce the HST–Gaia reference-frame uncertainties by another factor of ∼2, further improving the reference frame for dynamical studies.